SEBARAN UKURAN, POLA PERTUMBUHAN DAN FAKTOR KONDISI IKAN BETOK Anabas testudineus (Bloch 1972) DI PERAIRAN RAWA KABUPATEN BANJAR, KALIMANTAN SELATAN - Eka Anto Supeni; Eko Sri Wiyono; Mochammad Riyanto; Mulyono Mulyono (BAWAL Widya Riset Perikanan Tangkap, 2025)
The climbing perch is a type of freshwater fish that can live in tropical and subtropical regions. This fish belongs to the blackfish group, which is a fish that is resistant to environmental changes. It is very tolerant of extreme environmental conditions and can survive in acidic and alkaline water conditions. This study aims to estimate the size distribution, length-weight relationship (growth pattern), and condition factors of climbing perch in swamp waters of Banjar Regency. Sample data of 204 individual were obtained from several villages that are inland fishing centers in Sungai Rangas Ulu, Sungai Batang, Tungkaran, Melayu Tengah, Melayu Ulu, and Mekar villages for April–July 2024. The analysis results obtained a distribution fish lengths ranging from 56–150 mm, while the range weights was between 2.8–65.88 grams with average 89.58 and 15.29 grams, respectively. The length-weight relationship equation W = 5.4e-06.L3.209 shows that fish growth pattern is allometric positive (b > 3). Based on the size of Lm, 116 individuals (56.87%) of climbing perch were caught in swamp waters of Banjar Regency, including fish were suitable catching.